Enantioselective Synthesis and Biological Evaluation of Sanglifehrin A and B and Analogs. Issue 31 (24th June 2021) - Chang, Chia‐Fu; Flaxman, Hope A.; Woo, Christina M.
Abstract: Sanglifehrin A and B are immunosuppressive macrocyclic natural products endowed with and differentiated by a unique spirocyclic lactam. Herein, we report an enantioselective total synthesis and biological evaluation of sanglifehrin A and B and analogs. Access to the spirocyclic lactam was achieved through convergent assembly of a key pyranone intermediate followed by a stereo‐controlled spirocyclization. The 22‐membered macrocyclic core was synthesized by ring‐closing metathesis in the presence of 2, 6‐bis(trifluoromethyl) benzeneboronic acid (BFBB). The spirocyclic lactam and macrocycle fragments were united by a Stille coupling to furnish sanglifehrin A and B. Additional sanglifehrin B analogs with variation at the C40 position were additionally prepared. Biological evaluation revealed that the 2‐CF3 analog of sanglifehrin B exhibited higher anti‐proliferative activity than the natural products sanglifehrin A and B in Jurkat cells. Both natural products induced higher‐order homodimerization of cyclophilin A (CypA), but only sanglifehrin A promoted CypA complexation with inosine‐5′‐monophosphate dehydrogenase 2 (IMPDH2). The synthesis reported herein will enable further evaluation of the spirolactam and its contribution to sanglifehrin‐dependent immunosuppressive activity. Abstract : The immunosuppressive natural products, sanglifehrin A and B, bearing a 22‐membered macrocycle appended with a unique highly‐substituted spirolactam, pose formidable challenges to synthetic accessibility and derivatization. A versatile strategy toward the spirolactam through convergent assembly of fully‐functionalized fragments culminated in the total synthesis of sanglifehrin A and sanglifehrin B and preparation of additional analogs at position C40 for evaluation of biological activity in Jurkat cells and stabilization of protein–protein interactions.